From Classroom to Campus: Strategic Models for Enhancing School–University Collaboration in Teacher Education - Amirsheibani, Morteza; Yo'ldoshev, Otabek Abdug'aniyevich (International Journal of Educational Research & Social Sciences, 2025)
As teacher education evolves to meet the demands of diverse, dynamic classrooms, the need for meaningful collaboration between universities and schools has become more urgent than ever. This study investigates the structural, functional, and relational components that underpin effective school–university partnerships in the preparation of pre-service teachers. Employing a convergent mixed-methods design, the research draws on survey data from 104 participants—including university educators, school mentors, and student teachers—alongside in-depth interviews and document analysis across multiple institutions. Findings reveal that while foundational elements such as strategic alignment and institutional support are necessary, the long-term success of partnerships hinges on enabling conditions like relational trust, informal communication, and leadership continuity. Based on these insights, the study proposes a three-layer strategic framework that integrates policy, practice, and interpersonal dynamics. This model not only illustrates the complexity of collaborative teacher education but also offers a practical guide for institutions seeking to build more sustainable and reciprocal partnerships. The study concludes by discussing implications for practice, equity in recognition, and directions for future research.